SYNERGISTIC EFFECT OF CURCUMA XANTHORRHIZA AND PHYSALIS ANGULATA EXTRACTS AS ANTIOXIDANTS AGAINST DPPH RADICALS - Setiawan, Putu Yudhistira Budhi; Hita, I Putu Gede Adi Purwa; Ardinata, I Putu Riska; Suryaningsih, Ni Putu Aryati (Journal Pharmaceutical Science and Application; Vol 5 No 2 (2023): Journal Pharmaceutical Science and ApplicationDO - 10.24843/JPSA.2023.v05.i02.p05, 2023)
Background: As a single extract, Curcuma xanthorrhiza and Physalis angulata are known to have antioxidant activity. However, the interaction effect of antioxidants in suppressing DPPH (2,2-difenil-1-pikrilhidrazil) radicals that arise in these two combinations of plant extracts is not yet known. In this study, the combination of these two plants was investigated for their antioxidant properties and synergistic effects. Objective: This study aims to determine the effect of the combination of Curcuma xanthorrhiza and Physalis angulata as antioxidants and the interactions they cause. Methods: The rhizomes of Curcuma xanthorrhiza and the herb Physalis angulata were extracted separately with ethanol. After evaporation, the crude xtract was tested individually to obtain the IC50 value. Based on the IC50 value of each extract, 9 combination variations were made and the combination index (CI) value was calculated to determine the resulting interaction effect. Result: The antioxidant activity of Curcuma xanthorrhiza IC50 extract is 51.015 ppm, higher than Physalis angulata IC50 extract which is 90.488 ppm. The CI value observed in the combination of extracts in all combinations had a CI value <1. Conclusion: This research shows that the combination of Curcuma xanthorrhiza rhizome extract and Physalis angulata herb has synergistic antioxidant properties. Keywords: Combination; Synergis; Antioxidant; Combination Index